Failure probability of F-100 Pratt & Whitney-220E turbofan engine on F-16 fighting falcon aircraft - Hanawa, Riski Riswandi; Rahmawati, Fajar Khanif; Prattiwi, Elisabeth Anna; Deny Kusumaningrum, Maria Asumpta; Kumolosari, Eli (Vortex, 2024)
Engine failure is a condition where the engine operates outside normal conditions. One of the abnormal conditions that occurs can be caused by a fault that occurs in each engine module. Engine module is one of the components on an aircraft that functions for supports the aircraft to fly and controls all engine operations, wether on the ground and during flight. The problem can occur in each engine module at any time causing engine failure. Therefore, it is necessary to carry out further analysis to determine the cause of the failure that occurred, as well as to implement appropriate mitigation measures. The method used is the Fault Tree Analysis (FTA) method, which is a method for identifying risks that contribute to failure and determining failure probability. From the analysis using the qualitative fault tree analysis method 71 events were obtained with 35 basic events. Meanwhile, the quantitative analysis produces a cumulative probability failure of 0.747. The probability value has almost reached 1, therefore preventive maintenance has to be carried out to prevent functional failure.